Pengaruh Variasi Jarak Tulangan Spiral Terhadap Perilaku Kolom Akibat Beban Aksial Konsentris Menggunakan Finite Element Analysis - Lutffeoneta, Aurora; Rosidawani, Rosidawani; Aminuddin, K. M. (Syntax Literate, 2025)
Columns are critical structural elements designed to resist axial loads and distribute them to underlying structural components. The use of spiral reinforcement as lateral confinement in cylindrical columns is known to enhance compressive strength and ductility. One of the parameters affecting the performance of spiral reinforcement is the spacing between the turns (pitch), which serves as lateral confinement. This study aims to investigate the effect of varying spiral reinforcement spacing on the stress and strain responses of cylindrical columns subjected to concentric axial loads, using finite element analysis (FEA). The modeling was conducted using Abaqus/CAE software, employing the Concrete Damaged Plasticity (CDP) model. Three different spiral reinforcement spacings were analyzed: 30 mm (K-30), 45 mm (K-45), and 60 mm (K-60). The numerical results include stress and strain responses, ductility, toughness, and failure patterns. The peak compressive strength (fcc) for K-30 was 70.960 MPa, for K-45 was 64.128 MPa, and for K-60 was 60.439 MPa. The toughness values were 1.508 J/mm3 for K-30, 1.796 J/mm3 for K-45, and 1.688 J/mm3 for K-60. The ductility values were 0.403 for K-30, 0.369 for K-45, and 0.394 for K-60. Observations of the failure pattern revealed that both K-30 and K-45 exhibited similar damage distributions, characterized by red-colored stress concentrations that were evenly distributed along the surface of the column cover. In contrast, K-60 showed damage primarily on the cover in the central area of the column.